Lembar Kerja Peserta Didik Berdasarkan Model Pembelajaran Generatif untuk Materi Gelombang Cahaya Kelas XI SMA - Alqadri, Dheo; Akmam, Akmam; Darvina, Yenni; Riyasni, Selma (Lembaga Yasin AlSys, 2024)
This research aims to develop LKPD based on a generative learning model on light wave material for class XI SMA that is valid and practical. The generative learning model was chosen because it is able to encourage students to actively build their understanding through interaction, reflection and discussion. This model has proven effective in improving critical thinking and problem-solving skills in physics learning. The developed worksheet is designed following the syntax of the generative learning model: orientation, cognitive conflict, disclosure, construct, application, and reflection, to support in-depth learning and link theory with real application. This research uses the Research and Development (R&D) method with the 4D development model (define, design, develop, disseminate). The define stage includes needs analysis and problem identification. At the design stage, the LKPD was designed by taking into account the content, structure, and aesthetic components. The development stage involves validity testing by experts, well as practicality testing by teachers and students. The dissemination stage is planned for wider application. The results showed that this LKPD has a very high level of validity with a validation index value of 0.94 in the content aspect and 0.86 in the structure aspect, which means that this LKPD meets the eligibility standards of the Merdeka curriculum. The practicality test shows that the LKPD is very practical with a teacher assessment score of 95% and a student assessment of 87%, so it is feasible to use it in the real field because it has been declared valid and practical.